Dementia risk reduction: why haven't the pharmacological risk reduction trials worked? An in‐depth exploration of seven established risk factors. Issue 1 (8th December 2021) - Peters, Ruth; Breitner, John; James, Sarah; Jicha, Gregory A.; Meyer, Pierre‐Francois; Richards, Marcus; Smith, A. David; Yassine, Hussein N.; Abner, Erin; Hainsworth, Atticus H.; Kehoe, Patrick G.; Beckett, Nigel; et al.
Abstract: Identifying the leading health and lifestyle factors for the risk of incident dementia and Alzheimer's disease has yet to translate to risk reduction. To understand why, we examined the discrepancies between observational and clinical trial evidence for seven modifiable risk factors: type 2 diabetes, dyslipidemia, hypertension, estrogens, inflammation, omega‐3 fatty acids, and hyperhomocysteinemia. Sample heterogeneity and paucity of intervention details (dose, timing, formulation) were common themes. Epidemiological evidence is more mature for some interventions (eg, non‐steroidal anti‐inflammatory drugs [NSAIDs]) than others. Trial data are promising for anti‐hypertensives and B vitamin supplementation. Taken together, these risk factors highlight a future need for more targeted sample selection in clinical trials, a better understanding of interventions, and deeper analysis of existing data.